Auxiliary liver transplantation for acute liver failure - Belghiti, J (2004)
Background In patients with acute liver failure (ALF) who fulfil criteria, liver transplantation is the only effective treatment which can substitute metabolic and excretory function of the liver. Auxiliary liver transplantation was developed because a significant minority of patients with ALF who fulfil transplant criteria can have a complete morphological and functional recovery of their liver. The favourable outcome reported in European series using auxiliary partial orthotopic liver transplantation (APOLT), the greater experience as well as the lessons from split liver and from living related donors have revived interest in this approach. In selected patients aged <40 years without haemodynamic instability, the use of ABO-compatible, non-steatotic grafts harvested from young donors with normal liver function can restore liver function and prevent the occurrence of irreversible brain damage. In the majority of cases the auxiliary graft is a right graft which is placed orthotopically after a right hepatectomy in the recipient. After standard immunosuppression, the recovery of the native liver is assessed by biopsies, hepatobiliary scintigraphy and computed tomography. When, on the basis of histological, scintigraphical and morphological data, there is evidence of sufficient regeneration of the native liver, immunosuppression can be discontinued progressively. Complete regeneration of the native liver can be observed in >50% of patients, who can be withdrawn from immunosuppression. Therefore the advantages of auxiliary transplantation seem to balance favourably with the potential inconvenience of this technique in selected patients.